A dandelion polysaccharide and its selenium nanoparticles: Structure features and evaluation of anti-tumor activity in zebrafish models - Zhang, Shaojie; Song, Ziteng; Shi, Lijuan; Zhou, Linan; Zhang, Jie; Cui, Jianlin; Li, Yuhao; Jin, Da-Qing; Ohizumi, Yasushi; Xu, Jing; Guo, Yuanqiang (Carbohydrate Polymers, 2021)
In this study, an inulin fructan (TMP50-2) with moderate anti-tumor activity was obtained from dandelion. To further improve the anti-tumor activity of TMP50-2, a monodisperse and stable spherical nanoparticle (Tw-TMP-SeNP, 50 nm) was fabricated. Physico-chemical analysis revealed that TMP50-2 and Tween 80 were tightly wrapped on the surface of SeNPs by forming CO⋯Se bonds or through hydrogen bonding interaction (OH⋯Se). In vitro anti-tumor assay showed that Tw-TMP-SeNP treatment could significantly inhibit the proliferation of cancer cells (HepG2, A549, and HeLa) in a dose-dependent manner, while HepG2 cells were more susceptible to Tw-TMP-SeNP with an IC50 value of 46.8 μg/mL. The apoptosis induction of HepG2 cells by Tw-TMP-SeNP was evidenced by increasing the proportion of apoptotic cells ranging from 12.5% to 27.4%. Furthermore, in vivo zebrafish model confirmed the anti-tumor activity of Tw-TMP-SeNP by inhibiting the proliferation and migration of tumor cells as well as the angiogenesis of zebrafish embryos. •An inulin fructan, TMP50-2, was purified and characterized from dandelion.•A fructan-based nanoparticle (Tw-TMP-SeNP) was designed, fabricated, and characterized.•Tw-TMP-SeNP exerted anti-tumor activity by inducing apoptosis.•Tw-TMP-SeNP blocked tumor proliferation and migration in the zebrafish xenograft model.•Tw-TMP-SeNP inhibited angiogenesis in the transgenic zebrafish model.